Alteração mastigatória, ambiente enriquecido e envelhecimento: estudos estereológicos de ca1 do hipocampo do camundongo suíço albino. - FELÍCIO, André Pinheiro Gurgel (2022)
To investigate possible influences of enriched environment on the changes of CA1 astrocytic laminar distribution induced by reduced mastication, female albino Swiss mice fed with soft diet (SD) or hard diet (HD) were housed from weaning either in impoverished conditions or in enriched conditions. After 6, 12 and 18 months brain hippocampal sections from both HD and SD animals were immunolabeled for glial fibrillary acid protein to identify astrocytes and a blind optical fractionator’s analysis was applied to assess possible changes in the laminar distribution. SD as compared to HD stereological estimations revealed that the laminar distribution of astrocytes in CA1 was differentially affected by reduced mastication and aging and these variables seem to produce addictive effects. Apart from stratum pyramydale where enriched environment seem to increase aging and masticatory effects of reduction in the number of astrocytes, in all other layers enriched environment seems to counteract the impact of masticatory deprivation and aging. Thus, differential effects on CA1 astrocytic laminar distribution were found as a function of masticatory deprivation, age and environment suggesting that at least two different profiles of astrocytes may be contributing to these events. Possible molecular mechanisms associated to these differences remain to be investigated.